Pengaruh Iklim Organisasi dan Kompetensi terhadap Motivasi Kerja Pustakawan pada Perpustakaan Universitas Sumatera Utara - Margaretha Serevina (Jurnal Pustaka Nusantara dan Budaya, 2013)
Abstract   This research had been done at USU Library. The objective of research were assesed and tested: 1) the influence of organization climate for librarian working motivation at USU Library, 2) the influence of competence for librarian working at USU Library, 3) climate organization and competence influence librarian working motivation at USU Library. The analytical method which are being used quantitative causal associate using multiple linear regression analysis. The results of this research showed that the results of the Ftest indicates that the variables consiting of organization climate and competencies can be used to estimate librarian working motivation at USU Library. Ttest results significantly (ttest) states that has a significant influence. Organization climate is variable independent, while the variable competence dependent must be increased again in order to estimate the librarian working motivation at USU Library. Ajusted R square results increase the librarian working motivation at USU Library can be explained by other variables which are not examined in this research.     Key Words: Organizational Climate, Job Competence and The librarian working motivation